UJI KUALITAS BATU BATA DI DESA HATU DAN LAHA SEBAGAI BAHAN KONSTRUKSI - Lilipaly, Aprilia Yunety; Roberth, Herry Henry; soumokil, Musper David (Jurusan Teknik Sipil, 2024)
Bricks are a building material that has long been known and used by people in both rural and urban areas and has the same function, namely as a construction material. Bricks are used for civil engineering applications such as walls and residential buildings, fences and also channels. Bricks are made from clay which are made using a simple mold made of wood. After being molded, the bricks are dried in the sun to dry. Once dry, the bricks are arranged neatly and burned at a fairly high fire temperature. This burning process can cause the bricks to become hard. This research was carried out to determine the quality of bricks in two villages, namely Hatu village and Laha village using physical and mechanical properties testing on printed brick samples. Based on the results of testing the physical properties in Hatu village, it was found that the specific gravity was 1.596, the bulk density was 14.7 gr, the porosity was 37.8% and in the Laha village the specific gravity was 1.811, 13.6 gr and 42.4%. Meanwhile, the mechanical test results for the bottom sample in Hatu village were 27.31 kg/cm2 and the bottom sample was 40.10 kg/cm2 and the results in the bottom sample village were 19.16 kg/cm2 and the results for the top sample were 18.02 kg/cm2.